Eksplorasi kinerja keuangan dan ukuran perusahaan terhadap corporate social responsibility di sektor energi Indonesia - Venansius, Vincent; Wenny, Cherrya Dhia (Nur Science Institute, 2025)
The study aims to determine the effect of financial performance and company size on corporate social responsibility in energy sector companies listed on the Indonesia Stock Exchange for 2021-2023. Data collection method by collecting annual financial reports on the IDX website. The number of samples used in this study was 38 from 83 energy companies listed on the Indonesia Stock Exchange; therefore, the number of research data analyzed was 114. The data analysis method used is Multiple Linear Regression. The study's findings indicate that the financial performance variable does not affect corporate social responsibility. At the same time, company size affects corporate social responsibility, and financial performance and company size do not simultaneously affect corporate social responsibility.